Ansätze zur Gewaltüberwindung in der Bibel. Drei alttestamentliche Beispiele - Siquans, Agnethe (Protokolle zur Bibel, 2009)
This essay exemplarily shows some strategies in dealing with violence in the Old Testament, which reflect human and divine use of force. In texts about Israel’s wars (1) violence is assigned to JHWH in different ways. JHWH acts in favour of his oppressed and powerless people. The divine command to accomplish the „ban“ (2) on certain people is subtly undermined in Deuteronomy and Joshua. The motif of God’s „repentance“ (3) is an extreme theological diction to express God’s faithfulness towards his people who do not repent and Israel’s possible salvation in face of the impending extermination by God himself. All these strategies do not overcome violence, but they are modes of reflection and relativisation of it.